Water Requirements and Irrigation Scheduling of Direct Seeded Rice-Wheat using CROPWAT Model - Vashisht, Amandeep; Satpute, Sanjay T. (Indian Journal of Hill Farming, 2016)
To conserve water, some form of irrigation scheduling should be used by the farming community. The simulation study was conducted with the objectives of determining irrigation water requirement and irrigation scheduling of directed seeded rice (DSR) and wheat irrigated by sprinkler irrigation system. The irrigation efficiency of 80% was considered for the study. From the study, for DSR, at 20% critical depletion, the total seasonal water requirement and irrigation requirement was found as 639.4 mm and 207.8 mm, respectively. The crop water requirement was same for 20%, 30% and 40% critical depletion because it was calculated on the basis of meteorological data. Due to change in critical soil moisture depletion from 20% to 30%, the effective rain efficiency found to increase from 42.9 % to 49.6%. Again due to change in critical soil moisture depletion from 30% to 40%, the effective rain efficiency found to increase from 49.6% to 52.2%. Due to change in effective rain efficiency, the actual irrigation requirement varied from 321.4 mm at 20% critical depletion to 252.7 mm at 40% critical depletion. Results revealed that the irrigation should be done at 40% critical depletion to achieve 0% yield reduction. In case of wheat, the total seasonal water requirement and irrigation requirement was found as 411 mm and 334 mm, respectively. The actual water use by the crop was 407.7 mm at 92.4 % rainfall efficiency considering 50% critical depletion. The actual irrigation requirement was found to be 252.7 mm. Irrigation should be done at the critical depletion to achieve 0% yield reduction of wheat and maximum rainfall efficiency. Results also revealed that the irrigation flow requirement for wheat found maximum in the month of March, i.e. 0.52 l/s/ha whereas the irrigation flow requirement for DSR found maximum in the month of August, i.e. 0.24 l/s/ha.